Mastering Enterprise Java Beans - Ed Roman (Mc Graw Hill, 2005)
This book is a tutorial on Enterprise JavaBeans (EJB). It's about concepts, methodology, and development. This book also contains a number of advanced EJB topics, giving you a practical and real-world understanding of the subject. By reading this book, you will acquire a deep understanding of EJB.